Sperm DNA damage output parameters measured by the alkaline Comet assay and their importance. (6th May 2016) - Simon, L.; Aston, K. I.; Emery, B. R.; Hotaling, J.; Carrell, D. T.
Summary: The alkaline Comet assay has shown high diagnostic value to determine male reproductive health and prognostic ability to predict ART success. Here, spermatozoon was analysed in 47 fertile donors and 238 patients, including 132 couples undergoing ART [semen was collected: Group I – within 3 months of their treatment ( n  = 79); and Group II – 3 months prior to their treatment ( n  = 53)]. We introduce four Comet distribution plots (A, B1, B2 and C) by plotting the level of DNA damage ( x ‐axis) and percentage of comets ( y ‐axis). Fertile donors had low mean DNA damage, olive tail moment and per cent of spermatozoa with damage and increased type A plots. Comet parameters were associated with clinical pregnancies in Group I. About 66% of couples with type A distribution plot were successful after ART, whereas couples with type B1, B2 and C distribution plots achieved 56%, 44% and 33% pregnancies respectively. The efficiency of the Comet assay was due to complete decondensation process, where the compact sperm nuclear DNA (28.2 ± 0.2 μm 3 ) is decondensed to ~63 μm 3 (before lysis) and ~1018 μm 3 (after lysis). A combinational analysis of all the Comet output parameters may provide a comprehensive evaluation of patient's reproductive health as these parameters measure different aspects of DNA damage within the spermatozoa.